Pengaruh Kapitalisasi Pasar, Ukuran Perusahaan, Arus Kas Bebas, Kebijakan Dividen, dan Tingkat Suku Bunga terhadap Nilai Perusahaan - Lim, Jennifer; Supriyanto (Politeknik Negeri Jember, 2025)
This study aims to analyze the influence of market capitalization, firm size, free cash flow, dividend policy, and interest rates on firm value. The research employs a quantitative approach using regression analysis on secondary data of companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. The results indicate that market capitalization, free cash flow, and dividend policy have a positive effect on firm value, while firm size has a significant negative effect, and interest rates show no significant impact. These findings highlight the importance of financial and policy factors in determining firm value and provide practical implications for management in developing strategies to enhance firm value and attract investors.